A binational multicenter pilot feasibility randomized controlled trial of early goal-directed mobilization in the ICU. - Hodgson, C.; Bailey, M.; Bellomo, R.; Berney, S.; Buhr, H.; Denehy, L.; Gabbe, B.; Harrold, Megan; Higgins, A.; Iwashyna, T.; Papworth, R.; Parke, R.; et al. (Lippincott Williams & Wilkins, 2016)
Objectives: To determine if the early goal-directed mobilization intervention could be delivered to patients receiving mechanical ventilation with increased maximal levels of activity compared with standard care.Design: A pilot randomized controlled trial.Setting: Five ICUs in Australia and New Zealand.Participants: Fifty critically ill adults mechanically ventilated for greater than 24 hours.Intervention: Patients were randomly assigned to either early goal-directed mobilization (intervention) or to standard care (control). Early goal-directed mobilization comprised functional rehabilitation treatment conducted at the highest level of activity possible for that patient assessed by the ICU mobility scale while receiving mechanical ventilation.Measurements and Main Results: The ICU mobility scale, strength, ventilation duration, ICU and hospital length of stay, and total inpatient (acute and rehabilitation) stay as well as 6-month post-ICU discharge health-related quality of life, activities of daily living, and anxiety and depression were recorded. The mean age was 61 years and 60% were men. The highest level of activity (ICU mobility scale) recorded during the ICU stay between the intervention and control groups was mean (95% CI) 7.3 (6.3–8.3) versus 5.9 (4.9–6.9), p = 0.05. The proportion of patients who walked in ICU was almost doubled with early goal-directed mobilization (intervention n = 19 [66%] vs control n = 8 [38%]; p = 0.05). There was no difference in total inpatient stay (d) between the intervention versus control groups (20 [15–35] vs 34 [18–43]; p = 0.37). There were no adverse events.Conclusions: Key Practice Points: Delivery of early goal-directed mobilization within a randomized controlled trial was feasible, safe and resulted in increased duration and level of active exercises.